1992
DOI: 10.1152/physiologyonline.1992.7.2.56
|View full text |Cite
|
Sign up to set email alerts
|

ATP Receptor-Operated Ca2+ Influx and Catecholamine Release From Neuronal Cells

Abstract: The physiological function of extracellular ATP was investigated using PC-12 cells as a model neuronal cell. The mechanism of action of ATP proposed is that ATP stimulates P2-purinoceptors, activates Ca2+-permeable cation channels, and causes Ca2+ influx, triggering catecholamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…recorded from circular muscle of the guinea-pig fundus is also generated by stimulation of NANC nerves, and this potential can be blocked by apamin (Komori & Suzuki, 1986) or suramin (Ohno et al, 1993). Apamin is an inhibitor of Ca2+-activated K+-channels (Romey & Lazdunski, 1984), while suramin is an inhibitor of the ATP-receptor (Inoue & Nakazawa, 1992). Therefore, the NANC ij.p.…”
Section: Discussionmentioning
confidence: 99%
“…recorded from circular muscle of the guinea-pig fundus is also generated by stimulation of NANC nerves, and this potential can be blocked by apamin (Komori & Suzuki, 1986) or suramin (Ohno et al, 1993). Apamin is an inhibitor of Ca2+-activated K+-channels (Romey & Lazdunski, 1984), while suramin is an inhibitor of the ATP-receptor (Inoue & Nakazawa, 1992). Therefore, the NANC ij.p.…”
Section: Discussionmentioning
confidence: 99%
“…However, low-affinity electrostatic binding of TNP-ATP to phospholipids has been reported to be minimal (Moezydlowski and Fortes, 1981). We were also precluded from using reactive blue 2, an alternative P, receptor blocker (Inoue and Nakazawa, 1992) to quench the P, receptor component of ATP binding sites because it exhibited considerable intrinsic fluorescence, in the micromolar concentration range, over the wavelengths used for detection of TNP-ATP binding. The significant block of the stereocilia TNP-ATP binding (57%) by suramin is highly suggestive of specific binding of the TNP-ATP to P, purinoceptors localized to this region.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a role for able to depolarize cell membranes and thereby activate voltage-dependent Ca2 channels, Nakazavva and Inoue [3,4,8] have suggested that ATP-induced Ca2 intlux through these chan nels does not contribute to the regulation of [Ca2 ], in PC12 cells. They reasoned that Ca2 -dependent inactivation of Ca2 channels during the ATP-activated cation-selective current un derlies the lack of contribution of the voltagedependent Ca2 channels in the regulation of [Ca2'],.…”
Section: Introductionmentioning
confidence: 84%
“…ATP seems to act on these cells by binding to P:-purinergic receptors [3], During exposure of the cells to ATP the membrane potential is depolarized, even in the absence of extracellular Ca2 , due to activation of a large inward current mainly car ried by Na ions [5]. The depolarization in duced by 100 pA/ ATP reached near 0 mV [8J.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation